2014
DOI: 10.1016/s2213-2600(14)70185-7
|View full text |Cite
|
Sign up to set email alerts
|

Radiological correlates and clinical implications of the paradoxical lung function response to β2 agonists: an observational study

Abstract: Background Bronchodilator response is seen in a significant proportion of patients with chronic obstructive pulmonary disease (COPD). However, there are also reports of a paradoxical response (PR) to beta2-agonists, resulting in bronchoconstriction. Asymptomatic bronchoconstriction is likely far more common but there has been no systematic study of this phenomenon.We assessed theprevalence of PR in current and former smokers with and without COPD, and its radiologic correlates and clinical implications. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 32 publications
4
25
0
Order By: Relevance
“…In all participants, ΔFEV 1 and ΔFVC ranged from −20% to 27% (with a median value of 6.3%) and from −16% to 26% (with a median value of 3.8%), respectively. It is of note that two participants had a paradoxical response to the bronchodilator (≥12% and 0.2 L reduction in FEV 1 and FVC, respectively) 27 in terms of FVC fall, one participant in terms of FEV 1 fall, and one in terms of fall in both FEV 1 and FVC. As compared to Group 1, Group 2 showed significantly higher values for ΔFVC, but not for ΔFEV 1 ( Table 1 ).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…In all participants, ΔFEV 1 and ΔFVC ranged from −20% to 27% (with a median value of 6.3%) and from −16% to 26% (with a median value of 3.8%), respectively. It is of note that two participants had a paradoxical response to the bronchodilator (≥12% and 0.2 L reduction in FEV 1 and FVC, respectively) 27 in terms of FVC fall, one participant in terms of FEV 1 fall, and one in terms of fall in both FEV 1 and FVC. As compared to Group 1, Group 2 showed significantly higher values for ΔFVC, but not for ΔFEV 1 ( Table 1 ).…”
Section: Resultsmentioning
confidence: 88%
“…Our result is in line with the findings of a recent study in >10,000 patients with COPD, which reported a paradoxical response to bronchodilators in nearly 5% of participants. 27 Compared with white patients, a paradoxical response was twice as common in African American patients (7% vs 3%). In the multivariate analyses, African American ethnic origin, less emphysema, airway wall thickness, worse dyspnea, reduced exercise capacity, and a greater frequency of exacerbations were independently associated with a paradoxical response.…”
Section: Discussionmentioning
confidence: 96%
“…This significant reduction in lung function after the administration of a BD is termed paradoxical bronchoconstriction [32], and it has been previously reported to range between 0.5 and 1.5% according to the fixed and GLI-LLN cut-offs, respectively [33,34]. In another study, paradoxical responses were noted in 5% of the patients, and their frequency was similar in those with COPD and in smokers without AO [35]. This phenomenon was also independently associated with COPD intermediate endpoints, including reduced exercise capacity, increased dyspnoea and a greater frequency of exacerbations, and the authors assume it is an enigmatic COPD phenotype [35].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, paradoxical responses were noted in 5% of the patients, and their frequency was similar in those with COPD and in smokers without AO [35]. This phenomenon was also independently associated with COPD intermediate endpoints, including reduced exercise capacity, increased dyspnoea and a greater frequency of exacerbations, and the authors assume it is an enigmatic COPD phenotype [35]. …”
Section: Discussionmentioning
confidence: 99%
“…Despite this important clinical association of the ATS/ERS BDR criteria50 , when we excluded BDR positive participants by ATS/ERS criteria, we observed that clinical associations of BDR Grading Strategy persisted for 6MWD, SGRQ and mMRC in the adjusted multivariable analysis: patients with greater BDR had greater exercise performance, better quality of life and less dyspnea perception (Table 5).We observed that 21.1% of our study group had a negative response (defined as ≤0.00% or ≤0.00L FEV1 change) to albuterol. Recently, Bhatt and colleagues showed that a paradoxical response to beta-2 agonists resulting in bronchoconstriction was associated with respiratory morbidity measured by higher mMRC, frequent exacerbations and lower 6MWD52 . Probably, some of the participants in negative response category in our study can be regarded to have a paradoxical response to beta-2 agonists.…”
mentioning
confidence: 99%